2020
DOI: 10.26508/lsa.201900576
|View full text |Cite
|
Sign up to set email alerts
|

ER-resident sensor PERK is essential for mitochondrial thermogenesis in brown adipose tissue

Abstract: Mitochondria play a central role in the function of brown adipocytes (BAs). Although mitochondrial biogenesis, which is indispensable for thermogenesis, is regulated by coordination between nuclear DNA transcription and mitochondrial DNA transcription, the molecular mechanisms of mitochondrial development during BA differentiation are largely unknown. Here, we show the importance of the ER-resident sensor PKR-like ER kinase (PERK) in the mitochondrial thermogenesis of brown adipose tissue. During BA differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 60 publications
8
33
0
Order By: Relevance
“…This PERK phosphorylation induces transcriptional activation by GA-binding protein transcription factor α subunit (GABPα), which is required for mitochondrial inner membrane protein biogenesis. This study also demonstrated that p-PERK controls mitochondrial and thermogenic gene expression via transcriptional activation by GABPα and UCP1-mediated thermogenesis in vitro and in vivo [164].…”
Section: Perksupporting
confidence: 58%
“…This PERK phosphorylation induces transcriptional activation by GA-binding protein transcription factor α subunit (GABPα), which is required for mitochondrial inner membrane protein biogenesis. This study also demonstrated that p-PERK controls mitochondrial and thermogenic gene expression via transcriptional activation by GABPα and UCP1-mediated thermogenesis in vitro and in vivo [164].…”
Section: Perksupporting
confidence: 58%
“…In a series of related recent papers, notably the most recent report by Latorre-Muro et al [2], as well as in a paper by Kato et al [3], this plasticity of BAT has been used as a means to delineate the molecules that direct cristae formation, not only in brown adipocytes but probably in all cells in the body (see also Balsa et al [4]). Because many mitochondrial proteins are synthesized in the endoplasmic reticulum (ER), it is perhaps not so surprising that a kinase in the ER that is located at mitochondria-associated ER membranes (MAMs) directs the process.…”
mentioning
confidence: 99%
“…They also found that PERK stimulated cristae formation, but this took place via another pathway. PERK was then seen to be physiologically phosphorylated independently of the ER stress pathway, and was found to be of importance for cristae formation also in brown adipocytes, although the mechanism remained undefined [3]. Latorre-Muro and colleagues [2] have now identified the alternative pathway by which PERK accomplishes this activation of cristae formation.…”
mentioning
confidence: 99%
See 2 more Smart Citations